2020
DOI: 10.3390/nu12123856
|View full text |Cite
|
Sign up to set email alerts
|

A Posteriori Dietary Patterns and Rheumatoid Arthritis Disease Activity: A Beneficial Role of Vegetable and Animal Unsaturated Fatty Acids

Abstract: To our knowledge, no studies have investigated the relationship between a posteriori dietary patterns (DPs)—representing current dietary behavior—and disease activity in patients with rheumatoid arthritis (RA). We analyzed data from a recent Italian cross-sectional study including 365 RA patients (median age: 58.46 years, 78.63% females). Prevalent DPs were identified through principal component factor analysis on 33 nutrients. RA activity was measured according to the Disease Activity Score on 28 joints (DAS2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Analyzing dietary patterns (rather than foods or nutrients) has been recommended as an effective method for studying diet and its relationship to health due to the complex interaction between different food components [ 26 , 27 ]. Dietary patterns can be derived using an a priori (hypothesis-driven) [ 28 ] or an a posteriori (data-driven) approach [ 18 , 29 , 30 ]. Although data-driven dietary patterns may not be as polarized as hypothesis-driven dietary patterns, they can more accurately reflect actual eating habits as combinations of food consumed in different groups of the population, rather than relying on current knowledge [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing dietary patterns (rather than foods or nutrients) has been recommended as an effective method for studying diet and its relationship to health due to the complex interaction between different food components [ 26 , 27 ]. Dietary patterns can be derived using an a priori (hypothesis-driven) [ 28 ] or an a posteriori (data-driven) approach [ 18 , 29 , 30 ]. Although data-driven dietary patterns may not be as polarized as hypothesis-driven dietary patterns, they can more accurately reflect actual eating habits as combinations of food consumed in different groups of the population, rather than relying on current knowledge [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the amount of PUFAs was most strongly related to the consumption of walnuts and linoleic and alpha-linolenic acids, acting as possible confounding factors. In this study, consumption of PUFAs was associated with a lower degree of disease activity according to Disease Activity Score on 28 joints (DAS28), independently of antibody positivity and with higher protection in more severe or chronic forms of the disease [ 362 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increased content of the n -6 PUFA LA in the RBC membrane was found associated with reduced risk of developing RA in the EPIC cohort [ 11 ]. In a cross-sectional study of patients with confirmed RA, a dietary pattern characterized by high consumption of vegetable-derived FA (ALA and LA) was associated with reduced risk of active disease [ 37 ]. However, LA was not a main contributor to pattern ω6 in this study.…”
Section: Discussionmentioning
confidence: 99%